An investigation into mechanisms of non-ionic surfactant effect on epithelial cells - Cavanagh, Robert (2018)
Amphipathic, non-ionic surfactants are widely used in pharmaceutical and food industries to enhance product features; as pharmaceutical excipients they achieve increased cell membrane permeability and consequently can improve the oral absorption of drugs across the intestinal epithelial barrier. The use of non-ionic surfactants has grown rapidly, and is predicted to increase, however, the mechanism(s) surrounding the induction of surfactant toxicity is not well established and, consequently, the potential risks of surfactant exposure are not well understood.